Algebra 2 (1st Edition)

Published by McDougal Littell
ISBN 10: 0618595414
ISBN 13: 978-0-61859-541-9

Chapter 5 Polynomials and Polynomial Functions - 5.9 Write Polynomial Functions and Models - 5.9 Exercises - Skill Practice - Page 397: 3



Work Step by Step

Here, we have $f(x)=a (x+1)(x-2)(x-3)$ When $x=0$, then we have $3=a (0+1)(0-2)(0-3)$ or, $6a=3$ This gives: $a=\dfrac{1}{2}$ Thus, we have $f(x)=\dfrac{1}{2}(x+1)(x-2)(x-3)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.